The Changing Evolution Aspiration of Experienced Employee form Project Engineering Units due to Globalization and its impact on attrition of experienced employees in selected Project Engineering Industrial Units in Pune. - .T.Patgar, Chandrashekar, (International Journal of Scientific Research and Management (IJSRM), 2016)
Industrial Units engaged in Engineering Purchase & Contract business operating in multiple domain for several years in Punewith loyal experienced employeesDue to globalization many multinational company established the base in Pune. They were eager to recruit these experiencedemployees to expand their business and offered innovative Human resource practice.Due to this there was a change in aspiration of the experienced employees from the Project Engineering Industries.Hence there was attrition of experienced employees in these project engineering industries.